Towards the co-construction of a dynamic hypermedial device for the process of writing scientific research articles in Spanish for graduate students - Tramallino, Carolina Paola (2023)
This article presents the results of the first diagnostic stage of a project that aims to co-design a dynamic hypermedia device that assists in the process of writing scientific papers in Spanish. These processes are conceived as social practices linked to specific knowledge and, in this sense, the research is framed in the development of Mediatised Educational Practices. Specifically, it develops the main problems presented by 100 postgraduate students at an Argentinean university in scientific-academic literacy linked to the development of written, research, and digital communicative competence. The methodology follows a qualitative-quantitative approach for analyzing the answers obtained through the questionnaire instrument. The results show that the main problem is the presentation and organization of the information; the lack of academic/specific vocabulary as well as difficulties in giving cohesion to the text and structuring it according to the characteristics of the genre. As for the expectations generated by assistive digital tools, it is made explicit that it should have forums and the possibility of obtaining immediate response assistance for queries arising in the writing process, and therefore it is suggested the existence of dictionaries of academic vocabulary, among other applications.